Psychological Analysis in Jhon Updike’s Separating - Yeni Wulan Dari (Journal of English Education, Literature and Linguistics, 2020)
ABSTRACTResearch objectives of psychological analysis in short stories Separated by Jhon Updike is to explore the true characteristics of the male lead character named Richard. My research on the psychological aspects of Richard. Psychology is related to someone mental. This is what I raised in the story of Separating. Psychology is very important in our life. Every healthy person is of course happy, but what will happen to the health of someone who is experiencing mental stress.Mental pressure and psychology disorders can be caused by many factors. In the story the main separating factor that causes chaos occurs is divorce and feeling unhappy despite having everything. Someone's dissatisfaction sometimes makes the person forget the real happiness. This was experienced by Richard he felt not happy even though he already had a wife and child.